Analisis Kinerja Keuangan Pajak Daerah Berdasarkan Metode Value For Money Pada Badan Pengelola Pajak Dan Retribusi Daerah Kota Medan Tahun 2016-2020 - Rizky Nurul Huda; Muhammad Arif; Kusmilawaty Kusmilawaty (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The background of this research is that tax collection is less than optimal by government agencies and the low revenue from parking fees is still low, even though parking fees are a potential tax sector if the government continues to maximize its collection. This is what causes a decrease in revenue because revenue targets are not realized properly. The aim of this research is to find out the condition of local tax financial performance as measured using the value for money method through economic ratios, efficiency ratios, and effectiveness ratios. The research was conducted at the Medan City Regional Tax and Retribution Management Agency. And using a qualitative descriptive approach, with data collection techniques, namely interviews and documentation, and the data analysis technique used is descriptive analysis. The results in this study indicate that the measurement of the Economic Ratio is in the Less Economical criteria by obtaining an average value of 72.62%, this shows that the Medan City BPPRD cannot carry out cost management in an economical way. The measurement of the Efficiency Ratio is in the Very Efficient criteria with an average of 9.16% obtained, these results show that the financial performance of the Medan City BPPRD is very efficient. The measurement of the Effectiveness Ratio is in the Very Effective criteria by obtaining an average value of 110.33%. This shows that the Medan City BPPRD has succeeded in managing its performance.